Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(x:3\dfrac{5}{6}=2\dfrac{8}{15}\)
\(x:\dfrac{23}{6}\) = \(\dfrac{38}{15}\)
\(x=\dfrac{38}{15}\times\dfrac{23}{6}\)
\(x=\dfrac{437}{45}\)
b, \(\dfrac{12}{15}:x+\dfrac{4}{3}=3\dfrac{2}{3}\)
\(\dfrac{12}{15}:x+\dfrac{4}{3}=\dfrac{11}{3}\)
\(\dfrac{12}{15}:x=\dfrac{11}{3}-\dfrac{4}{3}\)
\(\dfrac{12}{15}:x=\dfrac{7}{3}\)
x= \(\dfrac{12}{15}:\dfrac{7}{3}=\dfrac{12}{35}\)
\(c)x:\dfrac{5}{4}=\dfrac{9}{5}+\dfrac{1}{2}\)
\(x:\dfrac{5}{4}=\dfrac{23}{10}\)
\(x=\dfrac{23}{10}\times\dfrac{5}{4}\)
\(x=\dfrac{23}{8}\)
a) (x - 1) + (x + 2) + (x - 3) + (x + 4) + (x - 5) + (x + 6) = 21
x - 1 + x + 2 + x - 3 + x + 4 + x - 5 + x + 6 = 21
6x + 3 = 21
6x = 21 - 3
6x = 18
x = 18 : 6
x = 3
b) (x - 1) + (x + 3) + (x - 5) + (x + 7) + (x - 9) + (x + 11) = 186
x - 1 + x + 3 + x - 5 + x + 7 + x - 9 + x + 11 = 186
6x + 6 = 186
6x = 186 - 6
6x = 180
x = 180 : 6
x = 30
A=(6 : 35−116 x 67) : (415 x 1011+5211)A=(6 : 35−116 x 67) : (415 x 1011+5211)
A=(6 : 35−76 x 67) : (215 x 1011+5711)A=(6 : 35−76 x 67) : (215 x 1011+5711)
A=(10−1) : (4211+5711)A=(10−1) : (4211+5711)
A=9 : 9A=9 : 9
A=1
\(5\frac{9}{10}:\frac{3}{2}-\left(2\frac{1}{3}x4\frac{1}{2}-2\frac{1}{2}\right):\frac{7}{4}\)
=\(\frac{59}{10}:\frac{3}{2}-\left(\frac{7}{3}x\frac{9}{2}-\frac{5}{2}\right):\frac{7}{4}\)
=\(\frac{118}{30}-\left(\frac{63}{6}-\frac{5}{2}\right)x\frac{4}{7}\)
=\(\frac{118}{30}-\left(\frac{63}{6}-\frac{15}{6}\right)x\frac{4}{7}\)
=\(\frac{118}{30}-8x\frac{4}{7}\)
=\(\frac{118}{30}-\frac{32}{7}\)
sau bn tự tính nha
a) X x 2 + X x 3 = 4
X x (2 + 3) = 4
X x 5 = 4
x = 4 : 5
x = 0,8
b) X x 9 - X x 5 = 23
X x (9 - 5) = 23
X x 4 = 23
X = 23 : 4
X = 5,75
a, 2x+3x=4 \(\Rightarrow\)5x=4 =>x=\(\frac{4}{5}\)
b, 9x-5x=23 => 4x=23 => x=\(\frac{23}{4}\)
Bài 1: 1/3+1/9+1/27+1/81+1/243+1/729
Đặt:
A = 1 + 1/3 + 1/9 + 1/27 + 1/81 + 1/243 + 1/729
Nhân A với 3 ta có:
\(Ax3=3+\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}+\frac{1}{243}\)
\(\Rightarrow Ax3-S=3-\frac{1}{243}\)
\(\Rightarrow2A=\frac{2186}{729}\)
\(\Rightarrow A=\frac{2186}{729}:2\)
\(\Rightarrow A=\frac{1093}{729}\)
1. 41/7 - x = 25/9
=> x = 41/7 - 25/9
=> x = 194/63
2. 3x = 12,8
=> x = 12,8 : 3
=> x = 64/15
3. 41/2 x = 5
=> x = 5: 41/2
=> x = 10/41
4. 3/4 x = 1
=> x = 1: 3/4
=> x = 3/4
5. 4/5 : x = 3
=> x = 4/5 : 3
=> x = 4/15
6. 12/x = 4
=> x = 12/4
=> x = 3
7. 4/7 : x = 4/7
=> x = 4/7 : 4/7
=> x = 1
8. 2x - 3/4 = 7/8
=> 2x = 7/8 + 3/4
=> 2x = 13/8
=> x = 13/8 : 2
=> x =13/16
Ruby Chan :))
1, \(4\frac{1}{7}-x=2\frac{5}{9}\)
\(\frac{4\times7+1}{7}-x=\frac{2\times9+5}{9}\)
\(\frac{29}{7}-x=\frac{23}{9}\)
\(x=\frac{29}{7}-\frac{23}{9}\)
\(x=\frac{261}{63}-\frac{161}{63}\)
\(x=\frac{100}{63}\)
2, \(3\times x=12,18\)
\(x=12,18\div3\)
\(x=4,06\)
3, \(4\frac{1}{2}\times x=5\)
\(\frac{4\times2+1}{2}\times x=5\)
\(\frac{9}{2}\times x=5\)
\(x=5\div\frac{9}{2}\)
\(x=\frac{5\times2}{9}=\frac{10}{9}\)
4, \(\frac{3}{4}\times x=1\)
\(x=1\div\frac{3}{4}\)
\(x=\frac{1\times4}{3}=\frac{4}{3}\)
5, \(\frac{4}{5}\div x=3\)
\(x=\frac{4}{5}\div3\)
\(x=\frac{4}{5\times3}=\frac{4}{15}\)
6,\(\frac{12}{x}=4\)
\(x=12\div4\)
\(x=3\)
7, \(\frac{4}{7}\div x=\frac{4}{7}\)
\(x=\frac{4}{7}\div\frac{4}{7}\)
\(x=1\)
8, \(2x-\frac{3}{4}=\frac{7}{8}\)
\(2x=\frac{7}{8}+\frac{3}{4}\)
\(2x=\frac{7}{8}+\frac{6}{8}\)
\(2x=\frac{13}{8}\)
\(x=\frac{13}{8}\div2\)
\(x=\frac{13}{8\times2}=\frac{13}{16}\)
\(\dfrac{3}{5}\times\dfrac{5}{9}+\dfrac{3}{5}\times\dfrac{4}{9}=\dfrac{1}{3}+\dfrac{4}{15}=\dfrac{5}{15}+\dfrac{4}{15}=\dfrac{9}{15}=\dfrac{3}{5}\)